Multiple Attribute Group Decision Making for Plant Location Selection with Pythagorean Fuzzy Weighted Geometric Aggregation Operator - Rahman, K.; Khan, M.S. A.; Ullah, Murad; Fahmi, A. (The Nucleus, 2017)
There are many aggregation operators and applications have been developed up to date, but in this paper we present the idea of Pythagorean fuzzy weighted geometric aggregation operator, and also discuss some of their basic properties. At the last we give an application of this proposed operator. For this purpose we construct an algorithm and also construct a numerical example.